Decriminalisation Against Women Who Perform Illegal Abortions From the Islamic law Perspective - Ramadhita, Ramadhita; Hamidah, Tutik; Arfan, Abbas; Badruzzaman, Badruzzaman (Hukum Keluarga Islam IAIN LANGSA, 2023)
Illegal abortion remains a problem in many countries, medically, ethically and legally. Although it restricts the practice of abortion, Islamic law does not question its legality. This study aims to analyse the criminalisation of abortion in Islamic criminal law after 120 days of pregnancy. This article is a normative legal research with a conceptual approach. The results of this study indicate that Islamic law gives full respect to the right to life of a person, including the right to life of the foetus. However, Islamic legal scholars differ on the priorities in safeguarding the lives of pregnant women and foetuses. Islamic legal scholars differ on the criminalisation of abortion. For abortions performed under 120 days of age, the perpetrator is not subject to criminal sanctions. Abortion above 120 days is prohibited except where there are compelling medical, ethical and legal reasons to do so. In cases of rape that result in pregnancy, women have the full right to abortion at any gestational age. Nevertheless, women are still subject to sanctions in the form of kaffarat and diyat al-ghurrah. This aims to prevent people from easily performing abortions.